Embedded Ni–Ti particles for the detection of fatigue crack growth in AA7050. Issue 6 (29th February 2016) - Leser, W P; Newman, J A; Hochhalter, J D; Gupta, V K; Yuan, F G
Abstract: A multi‐functional aluminium alloy 7050 (AA7050) containing embedded Ni–Ti shape memory alloy particles to detect fatigue crack growth is proposed. The regions of intense strain near the tip of a growing fatigue crack cause nearby Ni–Ti particles to undergo a solid‐state phase transformation from austenite to martensite, releasing a detectable acoustic emission signal that can be used to locate the crack in the monitored component. The AA7050/Ni–Ti composite was made by vacuum hot pressing Ni–Ti powder between rolled AA7050 plates. The effect of hot pressing temperature and subsequent heat treatments (solutionizing and peak ageing) on the Ni–Ti particles was studied. A successful proof‐of‐concept was demonstrated for AA7050 with embedded particles that emit a measureable and repeatable acoustic emission signal in the presence of a fatigue crack, allowing for quick diagnosis of fatigue crack damage in this material.